The Law of Small Things : Creating a Habit of Integrity in a Culture of Mistrust. - Brody, Stuart H. (Berrett-Koehler Publishers, Incorporated, 2019)
Refuting the usual definitions of integrity, this book will demonstrate how to practice truthfulness in order to build trust and to create a habit of integrity that can transform our lives and our nation. --